Biological indicators of exposure to total and respirable aluminium dust fractions in a primary aluminium smelter. - Röllin, H B (1996)
OBJECTIVES: The study attempts to define biological indicators of aluminium uptake and excretion in workers exposed to airborne aluminium compounds in a primary aluminium smelter. Also, this study defines the total and respirable aluminium dust fractions in two different potrooms, and correlates their concentrations with biological indicators in this group of workers. METHODS: Air was sampled at defined work sites. Non-destructive and conventional techniques were used to find total and respirable aluminium content of the dust. Blood and urine was collected from 84 volunteers employed at various work stations throughout the smelter and from two different cohorts of controls matched for sex, age, and socioeconomic status. Aluminium in serum samples and urine specimens was measured by flameless atomic absorption with a PE 4100 ZL spectrometer. RESULTS: The correlation of aluminium concentrations in serum and urine samples with the degree of exposure was assessed for three arbitrary exposure categories; low (0.036 mg Al/m3), medium (0.35 mg Al/m3) and high (1.47 mg Al/m3) as found in different areas of the smelter. At medium and high exposure, the ratio of respirable to total aluminium in the dust samples varied significantly. At high exposure, serum aluminium, although significantly raised, was still within the normal range of an unexposed population. The workers with low exposure excreted aluminium in urine at levels significantly higher than the controls, but still within the normal range of the population. However, potroom workers with medium and high exposure had significantly higher urinary aluminium than the normal range. CONCLUSIONS: It is concluded that only urinary aluminium constitutes a practical index of occupational exposure at or above 0.35 mg Al/m3, and that the respirable fraction of the dust may play a major role in the biological response to exposure to aluminium in a smelter environment.